Anti-hyperglycemic activity of the leaves of Tetracera scandens Linn. Merr. (Dilleniaceae) in alloxan induced diabetic rats - Umar, Abdulrashid; Ahmed, Qamar Uddin; Muhammad, Bala Yauri; Dogarai, Bashar Bello S.; Mat So'ad, Siti Zaiton (Elsevier Science, Amsterdam, Netherlands., 2010)
Aim of the study: The present study was aimed to investigate the anti-diabetic potential of the leaves of Tetracera scandens Linn. Merr. (Dilleniaceae) in vivo with regard to prove its efficacy by local herbalists in the treatment of diabetes frailties. Materials and methods: Crude aqueous (AQ) and methanol (MEOH) extracts of the leaves of T. scandens L. were administered to both normal and alloxan induced diabetic male albino rats (Wistar strain). The blood glucose levels were measured at 0, 2, 4, 6 and 8 h after oral administration of AQ and MEOH extracts. Results: Significant reduction in glucose was observed in fasting blood glucose levels in the treated diabetic rats without causing any hypoglycemic effect compared to normal rats. Both polar extracts of the leaves of T. scandens L. exhibited significant anti-hyperglycemic activity at different doses and intervals. The highest anti-hyperglycemic effect (62.5%) was observed by the AQ extract at 0.25 g/kg body weight (b.w.) and MEOH extract (36.5%) at 0.5 g/kg b.w. after 8 h. The significant anti-hyperglycemic activity was found to be comparable with a known oral synthetic hypoglycemic drug, glibenclamide 0.25 mg/kg b.w. Conclusion: This study provides scientific evidence that the leaves of T. scandens L. have anti-diabetic efficacy and justifies its utility by local herbalists. However, more experiments at the clinical levels are required to confirm the utility of this plant by traditional practitioners in the management of diabetes mellitus.